An Empirical-Causative Analysis of the Politics of Xenophobia in South Africa - Akinrinde, Olawale Olufemi; Tar, Usman (Law Research Review Quarterly, 2021)
Several scholarly and scientific attentions have indeed been geared towards the studies on xenophobia in South Africa but little and very limited interrogation have been devoted to its precipitating politics. Extant works and studies on xenophobia in South Africa, in addition to their differing perspectives, have focused more on how to address the xenophobic reality rather than trying to understand why the politics of xenophobia has persisted unabatedly despite several remedial interventions from government and key stakeholders. This study bridges the gap by attempting to, very importantly, understand and advance reasons as to why the politics has continued against all efforts geared towards addressing it. While Brown Harrryâ€™s scapegoating thesis, Pillayâ€™s relative deprivation of South African blacks and Crushâ€™s cultural explanation amongst many others have attempted to offer empirical views on the manifestation of xenophobia in South Africa, that which is central to the understanding of the xenophobic phenomenon was innocently overlooked. The study therefore sees â€œpoliticsâ€ as being central to any attempt to understanding the manifestation of xenophobia in South Africa. The overwhelming scientific discourses and perspectives offered by this study on the politics of xenophobia would therefore help in bridging the gap in the extant literature and the body of knowledge.